Perancangan Prototipe Alat Monitoring serta Perekaman Data Secara Real-Time pada Controller BRT Juken 10 Berbasis Mikrokontroler ESP32 - Farizan Nurachman; Puput Winarti Rusimamto; Lilik Anifah; Sayyidul Aulia (INDO PUBLISHING, 2026)
The increasing use of converted electric motorcycles requires a monitoring system capable of continuously monitoring and recording vehicle operating conditions. The limited data logging capability of the BRT Juken 10 controller causes operational parameters and fault information that occur during vehicle operation to not be continuously documented. This study aims to design and implement a real-time monitoring and data logging prototype for the BRT Juken 10 controller based on the ESP32 microcontroller. The study employed an experimental engineering method through hardware implementation, microcontroller programming, functional testing, and prototype evaluation under operational conditions. Controller data were acquired through UART communication, while RPM, current, voltage, power, and fault status were displayed on a TFT LCD and automatically recorded on a microSD card in .csv format. The test results show that the prototype is capable of receiving, processing, displaying, and recording operational data in real time. Under normal operating conditions, the recorded data show relatively stable RPM, current without significant spikes, gradually decreasing voltage, and relatively constant power. The system is also capable of displaying connection status, microSD card condition, and fault information transmitted by the controller as preliminary information for fault diagnosis. Therefore, the developed prototype can be used as a monitoring and data logging system to support performance monitoring and preliminary fault analysis of electric motorcycles equipped with the BRT Juken 10 controller.